2020
DOI: 10.1002/pon.5534
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and severe mental illness: Bi‐directional problems and potential solutions

Abstract: Objective: Given the reported increased rates of physical morbidity and higher mortality rates among people with severe mental illness (SMI) (schizophrenia and severe mood disorders), with a life expectancy shorter of 15-20 years with respect to the general population, the aim of this paper was to call attention to the problem of cancer in SMI. Methods: We conducted a narrative review of the most significant papers published in the areas of cancer screening, incidence, mortality and palliative care in SMI. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 67 publications
8
72
2
Order By: Relevance
“…Consistent with previous reviews, 19,20,22,23 several issues related to stigma around mental disorders were identified in the present study.…”
Section: Issues Among Cancer Care Professionalssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous reviews, 19,20,22,23 several issues related to stigma around mental disorders were identified in the present study.…”
Section: Issues Among Cancer Care Professionalssupporting
confidence: 92%
“…People with mental disorders often experience problems such as lack of exercise, 26,27 poor eating habits, 26,28 obesity, 28,29 high rates of smoking or substance abuse, 26,[30][31][32][33][34] and low cancer-screening rates. [9][10][11][12] Consistent with previous papers, [19][20][21][22][23] the present study showed that these patients need support in the prevention and early detection of cancer.…”
Section: Patient Levelsupporting
confidence: 92%
“…functional impairments (e.g., affective, cognitive, perceptive), health care provider prejudice or fear of violent behavior or suicide, and disintegration of psychiatric and somatic medicine may contribute to this deficit. 23 This situation is unfortunate because psychological interventions have been evidenced to reduce distress significantly. 15,24 Moreover, psychological interventions usually increase treatment adherence 25 and satisfaction, 26,27 may be a mediator in the course and prognosis of cancer, 2,[28][29][30] reduce the length of hospitalizations, 31 reduce financial and emotional burden of health care providers 29 and maximize quality of life in general.…”
mentioning
confidence: 99%
“…Most likely, this is due to conservative documentation of mental disorders, which often occurs only when diagnoses are reported by referring/ consulting physicians or when patients disclose they have a mental disorder and allow inspection of treatment records. Mental disorders are often not discussed because patients and treatment teams fear stigmatization23 or because the focus is on physical symptoms.Second, there are many medical reasons for the prescription of psychopharmacology to patients with cancer, including the management of pain (antidepressants), vomiting (antipsychotics), or epileptic seizures (mood stabilizers). It would seem reasonable to exclude the administration of psychopharmacology for non-psychiatric reasons from the present analysis.…”
mentioning
confidence: 99%
“…Available data suggest an increased prevalence of physical illness which results in a life expectancy 15-20 years shorter among individuals with SMI than the general population. [1][2][3][4][5][6][7][8] Cancer has been indicated as one of the main culprits, not only because of its negative impact on quality of life and functioning, but also for the heavy toll it exerts on survival. 9 Preliminary investigations on cancer-related mortality were carried out in the 1980s.…”
Section: Introductionmentioning
confidence: 99%